Determinants of Mobile Banking Usage Decisions: The Moderating Role of Gender and Their Effects on Customer Satisfaction among HIMBARA Bank Customers in East Java - Endie Rianto; Slamet Riyadi; Sri Utami Ady (Journal of Economics and Management, 2026)
The rapid expansion of digital banking services has heightened the importance of understanding factors that influence mobile banking adoption and customer satisfaction. This study examines the effects of technology, knowledge, trust, security, ease of use, fast service, and perceived risk on mobile banking usage decisions and customer satisfaction among HIMBARA bank customers in East Java. The study also investigates the mediating role of usage decisions and the moderating role of gender. A quantitative survey approach was employed with 370 mobile banking users from Bank Mandiri, BRI, BNI, and BTN. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that technology, trust, security, ease of use, and fast service positively and significantly affect mobile banking usage decisions, while perceived risk has a significant negative effect. Knowledge does not significantly influence usage decisions. Customer satisfaction is significantly influenced by technology, knowledge, ease of use, and usage decisions. Furthermore, usage decisions mediate the relationships between technology, trust, security, ease of use, fast service, perceived risk, and customer satisfaction. No mediation effect is found between knowledge and customer satisfaction. The findings also reveal that gender does not moderate the relationship between usage decisions and customer satisfaction. This study contributes to the mobile banking literature by integrating the Theory of Buyer Behavior, Technology Acceptance Model, and Theory of Planned Behavior into a comprehensive framework. The findings offer actionable insights for banks in developing customer-oriented mobile banking strategies.